灰社会理论:一个初步的分析 - 谢立中 (社会学研究, 2001)
In this article,the author argues that a special kind of social organizations can be found in contemporary rural China,which are what may be called “grey societies”.They are known as such because they have some special qualities that differentiate them both from “white societies” and from “black societies”.As a piece of preliminary work,this paper provides a sketchy description of the main characteristics of this kind of social organizations and some comments on their formation causes,basic functions,social consequences,and various possibilities of the evolution of them.
Keywords: 灰社会; 理论